Evaluation of the Benefits and Risks of Introducing Ebola Community Care Centers, Sierra Leone - Adam J. Kucharski; Anton Camacho; Francesco Checchi; Ron Waldman; Rebecca F. Grais; Jean-Clement Cabrol; Sylvie Briand; Marc Baguelin; Stefan Flasche; Sebastian Funk; W. John Edmunds (Emerging Infectious Diseases, 2015)
In some parts of western Africa, Ebola treatment centers (ETCs) have reached capacity. Unless capacity is rapidly scaled up, the chance to avoid a generalized Ebola epidemic will soon diminish. The World Health Organization and partners are considering additional Ebola patient care options, including community care centers (CCCs), small, lightly staffed units that could be used to isolate patients outside the home and get them into care sooner than otherwise possible. Using a transmission model, we evaluated the benefits and risks of introducing CCCs into Sierra Leone’s Western Area, where most ETCs are at capacity. We found that use of CCCs could lead to a decline in cases, even if virus transmission occurs between CCC patients and the community. However, to prevent CCC amplification of the epidemic, the risk of Ebola virus–negative persons being exposed to virus within CCCs would have to be offset by a reduction in community transmission resulting from CCC use.